2015
DOI: 10.1177/0305735615594492
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disfavoured music on affect complexity in young adults

Abstract: The notion that a positive and negative affect can co-exist is described as affect complexity. According to the Dynamic Model of Affect, stressful events decrease affect complexity. This study examined whether disliked music acts on its listeners in a similar manner to stressful events. Young adults (N = 397), 191 non-fans of the heavy metal genre and 206 fans of this genre, were exposed to a popular heavy metal song. Positive and negative emotions were measured before and after the exposure. While the affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The findings also indicated that conflicts between prisoners about the type and volume of music could lead to aggravation, fights and even physical violence. These findings are consistent with other studies that cited the potential of unpleasant music to provoke anger (Gowensmith and Bloom, 1997) and found that disliked music increased the level of negative emotions and decreased the level of positive emotions (Bodner and Bensimon, 2016). Moreover, the connection between disliked music and conflict is expressed dramatically in its systematic use as a 'no-touch' instrument of torture in interrogation rooms (Cusick, 2006).…”
Section: Closeness and Conflicts Among Inmates Via Musicsupporting
confidence: 91%
“…The findings also indicated that conflicts between prisoners about the type and volume of music could lead to aggravation, fights and even physical violence. These findings are consistent with other studies that cited the potential of unpleasant music to provoke anger (Gowensmith and Bloom, 1997) and found that disliked music increased the level of negative emotions and decreased the level of positive emotions (Bodner and Bensimon, 2016). Moreover, the connection between disliked music and conflict is expressed dramatically in its systematic use as a 'no-touch' instrument of torture in interrogation rooms (Cusick, 2006).…”
Section: Closeness and Conflicts Among Inmates Via Musicsupporting
confidence: 91%